Cover Feature: Photochemical Study of a Three‐Component Photocyclic Initiating System for Free Radical Photopolymerization: Implementing a Model for Digital Light Processing 3D Printing (ChemPhotoChem 11/2019). Issue 11 (4th November 2019) - Metral, Boris; Bischoff, Adrien; Ley, Christian; Ibrahim, Ahmad; Allonas, Xavier
Abstract : The Cover Feature represents the photochemical cycle involved in a new three‐component initiating system based on safranine O. Upon green‐light exposure, initiating radicals are produced and start acrylate photopolymerization, making this system suitable for digital light processing (DLP) 3D printing of complex objects (such as an Eiffel Tower). More information can be found in the Article by B. Metral et al. on page 1109 in Issue 11, 2019 (DOI: 10.1002/cptc.201900167 ).